PERAN PENGASUH DALAM MENANGGULANGI KENAKALAN REMAJA DI PONDOK PESANTREN DARUSSALAM SENGKUBANG - Madro’i, Madro’i; Hifza , Hifza; Nashirun , Nashirun (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
The focus of this research is: the competence of caregivers on male students, the caregiver's method in overcoming juvenile delinquency in male students, the caregiver's programme in overcoming juvenile delinquency in male students at the Darussalam Sengkubang Islamic Boarding School. This research uses a qualitative approach and uses descriptive research. Data collection techniques through interviews, observation, and documentation. Data analysis uses an interactive analysis model which includes data reduction, data presentation, and conclusion drawing. The results of this study are as follows: 1) The competence of caregivers at the Darussalam Sengkubang Islamic Boarding School is mostly caregivers who have completed S1, S2 education, and some are memorising the Qur'an, have extensive experience in the world of education. Have an Islamic personality that is reflected in daily words and actions. Receive continuous training to become a professional caregiver and teacher. 2) The method used by caregivers in overcoming juvenile delinquency in male students at the Darussalam Sengkubang Islamic Boarding School is through preventive action (prevention), and repressive action (action so that the violation does not recur). 3) The caregiver's programme in overcoming juvenile delinquency in male students, namely: 1) Providing teaching and habituation about Islamic religious values. 2) Supervising and controlling the activities of santri. 3) Forming and holding extracurricular activities.